THE STRATEGY OF EMPOWERMENT SMALL AND MEDIUM ENTERPRISES IN THE EFFORT FOR INCREASING REVENUE AND MARKET - PRASETIO ARIWIBOWO (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
The development of SMEs sector, explicitly aimed at the efforts to realize the power of the nation-competitiveness in order to strengthen the global competitive economy. This research uses qualitative descriptive method to describe each variable analyzed. The analysis is SWOT analysis and Analytical Hierarchy Procees (AHP) to calculate any case the most preferred and influence the development of the empowerment of SMEs especially in terms of revenue and market expansion in Semarang based and questionnaire that sample scrambled by the author. Objectives and results of this study is to determine the priority of the strategy used by the Semarang city government and become the main reference for entrepreneurs of SMEs in Semarang to increase revenue and market share in the city of Semarang is improving managerial skills by improving capacity, work ethic, and the performance of the institution and the staff of the local government of Semarang, and increase community participation in the planning, implementation, and monitoring of development of SMEs.